Understanding wheat farmers’ climate change adaptation in the Middle East and North Africa: The role of socioeconomic factors and perceptions in decision-making - Behnam Mirgol; Bastien Dieppois; Jessica Northey; Jonathan Eden; Lionel Jarlan; Saïd Khabba; Michel Le Page; Gil Mahe (Journal of Agriculture and Food Research)
Climate change poses severe risks to food security, contributing to declining wheat yields in the Middle East and North Africa (MENA), where agriculture is a vital source of food, income, and employment. This study investigates climate change adaptation strategies among 250 randomly selected wheat farmers in Algeria, Iran, Iraq, Jordan, Morocco, and Tunisia. It explores the frequency, timeframe, effectiveness, and challenges of adaptation strategies, as well as the influence of socioeconomic factors and farmers' perceptions of climate change on their decision-making. Our findings show that farmers are highly aware of climate change and its impacts, with 97 % and 68–75 % of respondents accurately perceiving observed alterations in temperature and rainfall, respectively. In response, farmers have adopted various strategies, with a higher tendency towards adjustments in sowing dates (61 %), crop varieties (54 %), irrigation systems (49 %), and fertiliser types (44 %). Despite the perceived significant effectiveness of these strategies, financial constraints, lack of access to high-quality seeds and fertilisers, and inadequate government support hinder their implementation. We also found that younger, less experienced, more educated farmers, those managing larger and mechanised farms, and those accessing specialised agricultural publications tend to adopt a broader range of strategies. Additionally, farmers who perceived increased temperatures implemented more adaptive practices, while those who perceived decreased rainfall focused on irrigation and soil and water conservation strategies. Targeted policy interventions, such as affordable access to modern machinery, specialised training programs, and improved seed and fertiliser quality, are essential to overcoming barriers, enhancing farmers’ resilience to climate risks, and ensuring sustainable agricultural productivity.